Evaluation of Family Planning Attitudes of Medical Faculty Senior Students - Yıldız, Mücahit; Babacanoğlu, Mert (Turkey Health Literacy Journal, 2022)
Objective: In this study, it is aimed to determine the knowledge and attitudes of the senior medical faculty students about family planningand to obtain information about the factors that may be effective in this regard.Method: This descriptive study was conducted on 60 Gazi University Faculty of Medicine senior students who agreed to participate inthe study between November 26 and December 26, 2021. Results: 60% of the participants in the research are women and almost all of them (96,7%) are single. It is equivalent to the household income expenditure of half of the participants. The median family planning attitude scores of the intern doctors participating in the study was 151 (96-198). The median of the attitude score towards society was 67 (43-74), the median of the attitude score towards the methodswas 49,5 (28-55), and the median of the attitude score towards pregnancy was 36 (22-40).Conclusion: In the study, it was aimed to determine the family planning attitudes of the medical faculty students, and the family planningattitudes of the students participating in this study were evaluated as sufficient-developable. Gender was found to be a factor affectingfamily planning attitude. Marital status, number of siblings, education levels of parents, household income were found to be ineffective infamily planning attitudes of medical school students.
Keywords: Family planning; Intern doctor; Attitude assessment; Faculty of Medicine